The Power of Authentication of Notary Deed in Justice in Indonesia - Umi Maskanah; Dian Melinda Oktavia (Magister Kenotariatan Universitas Pasundan, 2020)
Next to examine the second possibility of the matter in the case of the creation of the notarial deed itself so that the problem with the legal position (the Authentic Deed) in the courts, can be modeled due to the notary's lack of caution, so that the Authentic Deed is declared invalid (vide article 263 paragraph (1) CRIMINAL CODE), and/or in the absence of negligence of applying article 39 and article 40, then the notary can be made a party (defendant or secondary defendant) in the plaintiff's lawsuit, because according to Article 65 UUJN, a notary is responsible for any deed made by that notary, even if the notary protocol has been handed over to the depository of the notary protocols. Then the notary liability does not end even though the notary has retired, so that at any time he can be held accountable for a deed made before. In addition, there is a consequence that faces a notarial deed that is proven not to apply Article 39 and article 40, so that its power of evidence (in the trial) becomes like a private deed. In practice, a notary is often drawn to participate in or act as a party to a criminal offence, such as putting false information in a notarial deed. It is an interesting matter to examine, because as it is known that a notarial deed as an Authentic Deed has the power of authenticating the deed as perfect, and binding for the judge to believe the contents of the notarial deed are true, in accordance with what has been explained by the parties in the deed, then in my opinion, a Notary cannot be drawn into participating in conducting or assisting in the criminal offence of providing false information in a notarial deed. Because the Notary in making an Authentic Deed is passive, but if it is proven after the examination by the Regional Supervisory Council, and the Regional Supervisory Council has allowed the Notary in question to be examined, then the Notary can be seated as the Defendant.